The Clay bird - Masuda, Tareka; Masuda, Kyatharina; Bablu, Nurul Islam; Farazi, Russell; Chattopadhyay, Jayanto; Prachy, Rokeya (Milestone Film & Video ; MK2 : TF1 Video, Distributed by New Yorker Video, 2006)
Set against the backdrop of Pakistan during the turbulent 1960s, a family is ripped apart by religious beliefs and civil war. A young boy from Bangladesh is sent away by his Muslim father to a Madrasah. He struggles to adapt to a harsh monastic life.